Coronary chronic total occlusions affect long‐term prognosis in heart failure with mildly reduced ejection fraction - Behnes, Michael; Schmidberger, Moritz; Mashayekhi, Kambis; Vadalà, Giuseppe; Moroni, Alice; Guiterrez‐Chico, Juan‐Luis; Ayoub, Mohamed; Christiansen, Evald Høj; Pyxaras, Stylianos; Bufe, Alexander; Krötz, Florian; Schmitt, Alexander; et al. (Journal of the American Heart Association, 2025)
Background - This study investigates the prevalence and prognostic impact of coronary chronic total occlusions (CTO) in patients with heart failure with mildly reduced ejection fraction (HFmrEF). Although coronary artery disease (CAD) represents the leading HF etiology in HFmrEF, data about CTO in this population are rare. - Methods - All consecutive patients with HFmrEF (ie, left ventricular ejection fraction 41%-49% with signs and/or symptoms of heart failure) undergoing invasive coronary angiography from 2016 to 2022 were included retrospectively. Patients with at least one CTO were compared to patients without CTO, further risk stratification was performed according to the extend of CAD. The primary end point was long‐term all‐cause mortality at 30 months (ie, median follow‐up). Secondary end points comprised of major adverse cardiac and cerebrovascular events (MACCE), HF‐related and cardiac rehospitalization at 30 months. Furthermore, the association of percutaneous coronary intervention (PCI) with long‐term outcomes was investigated. - Results - 71% of patients with HFmrEF (1545/2184, primary cohort) underwent invasive coronary angiography. In patients undergoing invasive coronary angiography related to the index hospitalization, CAD was present in 81% (836/1037, final cohort), with a corresponding rate of CTO at 17% (n=141). Coronary CTO was associated with the highest rate of the primary end point (33%) compared with non‐CTO (19%), single‐vessel (12%) and multivessel CAD (21%) in HFmrEF (P=0.001). Accordingly, HFmrEF patients with CTO had the highest rates of various secondary endpoints, including long‐term MACCE compared to non‐CTO patients (60% versus 32%, P=0.001). Successful CTO‐PCI was associated with improved long‐term survival (21% versus 38%; hazard ratio, 0.49 [95% CI, 0.24-0.99]; P=0.046). - Conclusions - Coronary CTO are common in HFmrEF with a significant impact on long‐term prognosis. - Registration - URL: https://www.clinicaltrials.gov; unique identifier: NCT0560339.
Online veröffentlicht: 22. August 2025
Gesehen am 04.11.2025